PENGARUH KUALITAS JASA TERHADAP KEPUASAN ANGGOTA KOPERASI SIMPAN PINJAM KARYA MURNI MEDAN - Saragih, Nawary (Jurnal Manajemen dan Bisnis, 2022)
The purpose of this study was to determine the effect of quality on the satisfaction of members of the Karya Murni Savings and Loans Cooperative Medan. The type of research used is descriptive and quantitative. The research sample was 96 respondents with the maximum sampling error sampling method from the population carried out randomly. The required data was collected through a questionnaire. The data analysis method used is multiple linear regression analysis. The results showed that the trend of the number of cooperative members, the remaining operating results and the total assets of the cooperative decreased, this happened because of the dissatisfaction of the members in terms of the loan interest rates offered were higher than other savings and loan cooperatives, the length of time span between the application and loan disbursement ( checking files, guarantees, checking guarantees) while the need for funds is urgent, there are many administrative costs (fee to become a member, notary deed fees, fees if members borrow, loan administration fees and the impact of the Covid-19 pandemic that makes members' businesses stand still and unable to do so). paying dues obligations and loan installments this makes members leave the cooperative. Based on the F-test, with a significant level of 0.000 F-table which is 2.58, meaning that service quality simultaneously has a positive and significant effect on member satisfaction. The results of the t-test, that the tangibles variable, has a positive effect on the satisfaction of the members of the cooperative, but it is not significant on the satisfaction of the members of the cooperative. While empathy has a negative effect on the satisfaction of the members of the cooperative, but it is significant on the satisfaction of the members of the cooperative. Seeing the weakness of the t-test of the tangible and empathy variables, it is suggested that the management of the cooperative needs to review it by providing a uniqueness that is different from other competitors so that members can enjoy the results that are felt to exceed expectations, so that members will be very satisfied and remain loyal to the services offered. by members of the Karya Murni Savings and Loans Cooperative Medan